2.645751311 (I did it on a scientific calculator, so sorry if they wanted you to show the work..)
Answer:
x=1,2
Step-by-step explanation:
x^2-3x+2=0
(x-1)(x-2)
x-1=0
x-2=0
x=1,2
X=-5, X=4 hope this helps
Answer:
Step-by-step explanation:
I think you have the question incomplete, and that this is the complete question
sin^4a + cos^4a = 1 - 2sin^2a.cos^2a
To do this, we can start my mirroring the equation.
x² + y² = (x + y)² - 2xy,
This helps us break down the power from 4 to 2, so that we have
(sin²a)² + (cos²a)² = (sin²a + cos²a) ² - 2(sin²a) (cos²a)
Recall from identity that
Sin²Φ + cos²Φ = 1, so therefore
(sin²a)² + (cos²a)² = 1² - 2(sin²a) (cos²a)
On expanding the power and the brackets, we find that we have the equation proved.
sin^4a + cos^4a = 1 - 2sin^2a.cos^2a
Answer:
2z + 4 = 8
Z = 2
Step-by-step explanation:
2z + 4 = 8
-4. -4
2z = 8
—- —
2. 2
z. =. 4
Easy Peasy! Hope this helped :) have great day!!